2023
DOI: 10.1093/bjsopen/zrad026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity on perioperative outcomes following gastrointestinal surgery: meta-analysis

Abstract: Background Obesity can pose perioperative challenges related to obesity-associated co-morbidities and technical factors. However, the true impact of obesity on postoperative outcomes is not well established and reports are conflicting. The aim was to perform a systematic review and meta-analysis to explore the effect of obesity on perioperative outcomes for general surgery procedures in distinct obesity subtypes. Methods A sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Over the years, several studies have been conducted on how body composition is related to diseases, and many clinicians have been interested in body composition. Studies have shown that obese patients demonstrate a higher incidence of postoperative major complications [3,4]. Additionally, previous research has shown that sarcopenia is a negative oncological factor in patients with cancer [5,6].…”
Section: Acnmmentioning
confidence: 99%
“…Over the years, several studies have been conducted on how body composition is related to diseases, and many clinicians have been interested in body composition. Studies have shown that obese patients demonstrate a higher incidence of postoperative major complications [3,4]. Additionally, previous research has shown that sarcopenia is a negative oncological factor in patients with cancer [5,6].…”
Section: Acnmmentioning
confidence: 99%